Reduction of adhesive stain defect in flexible printed circuit board on hot pressing process: A case study of electronic component factory - Srisang, Sakulkaew; Puajindanetr, Somchai (Engineering and Applied Science Research, 2015)
The objective of this research is a reduction of an adhesive stain defect in flexible printed circuit board in hot pressing process, the electronic factory. The manufacturing have been processing by sheet type of products with ninety-six pieces of flexible printed circuit boards. Causes of the problem include the before and internal hot pressing process. In process beginning times, the most right row of products between the cooling plate and the hot pressing machine has temperature 71.2◦C that is higher than glass transition temperature (Tg) 60◦C. Those products’ temperature lead to evaporate a polyimide adhesive before hot pressing process beginning. The internal hot pressing process include the preheat times and the pressure time. In the preheat time the problem is a gap between lower and upper plate, was under specification (Under 1 mm) and leaded to adhesive polyimide stain. In the actuality this time requires temperature and low pressure that mean a gap within 1 – 2 mm (between lower and upper plate). In pressure times the hot pressing plate surface is not flat and products are pressed by insufficient force that it lead to generate an adhesive stain on flexible printed circuit boards. That force is measured by the pre-scale paper and a result, RGB color, is provided. And then color density (From standard color sample) and RGB color (From pre-scale paper) is found out the relation by Photoshop program and multiple regression theory using. The formula is applied to compare with defect so as to find out the suitable color density (Defects reducing). The solving solutions is provided including the gap reduced adjustment between cooling plate and hot pressing machine before hot pressing process, the plate adjustment within specification in the preheat time and the pressing plate polishing in the pressure time. Results of study and solving are provide defect reduction from 24.4 percentage to 7.2 percentage of total study product.